Ukrainian universities in new realities: Strategies for preserving academic potential during the war - Yana Suchikova; Yuriy Danko (Problems and Perspectives in Management)
The war in Ukraine has been ongoing for 10 years, reshaping the lives of people, communities, institutions, and worldviews. The occupation of Crimea and significant parts of the Donetsk and Luhansk regions in 2014 marked the first wave of shocks for Ukraine's higher education system. The massive relocation of universities from these regions signaled the beginning of a new reality. During this time, frontline regions actively demonstrated their dedication to Ukraine.Universities transformed into volunteer hubs, collecting supplies, provisions, and protective equipment for the front. Students, faculty, and other staff became volunteers and joined the war effort.